2007
DOI: 10.1590/s0100-29452007000300027
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of genetic parameters for fruit yield and quality in custard apple progenies

Abstract: -Apparently, there are no custard apple cultivars defined for the northeastern region of Brazil. The establishment of breeding programs aimed at the selection of types from productive locations for later cloning is desirable. This work's objective was to evaluate the yield (during the first three crops) and quality (first crop) of fruits from 20 half-sibling custard apple tree progenies, selected from home orchards. An additional objective was to estimate genetic parameters for the traits evaluated. A micro sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 4 publications
1
4
0
2
Order By: Relevance
“…Low PCV and GCV values were also reported for TSS, pH of juice (Faten and Messaoud, 2014) [13] , leaf breadth, fruit diameter (Munde, 2011) [30] , while moderate PCV and GCV values were reported for leaf length, fruit length, TSS, days to maturity and pH of juice (Munde 2011) [30] . The same results were reported by Moraes et al (2005) on the progenies of yellow passion fruit and by Silva et al (2007) [34] on custard apple. However, Da Silva et al (2008) [8] found higher GCV values (= 115%) for some morphoagronomic and fruit quality traits in papaya.…”
Section: Resultssupporting
confidence: 87%
“…Low PCV and GCV values were also reported for TSS, pH of juice (Faten and Messaoud, 2014) [13] , leaf breadth, fruit diameter (Munde, 2011) [30] , while moderate PCV and GCV values were reported for leaf length, fruit length, TSS, days to maturity and pH of juice (Munde 2011) [30] . The same results were reported by Moraes et al (2005) on the progenies of yellow passion fruit and by Silva et al (2007) [34] on custard apple. However, Da Silva et al (2008) [8] found higher GCV values (= 115%) for some morphoagronomic and fruit quality traits in papaya.…”
Section: Resultssupporting
confidence: 87%
“…Segundo Kluge et al (2002) e Silva et al (2007) o ratio é utilizado como indicador para determinação do estádio de maturação do fruto, sendo um indicativo de qualidade, pois determina o balanço entre os sabores doce/ácido. Os frutos que foram armazenados sem embalagem não tiveram variação do ratio em função do tempo apresentando um ratio de 42,7 em média.…”
Section: Resultsunclassified
“…O SS médio encontrado no experimento é relativamente inferior ao SS da maioria das espécies de Annonaceae, que contêm aproximadamente 24 °Brix (NEVES; YUHARA, 2003;MARCELLINI et al, 2003;SILVA et al, 2007). Porém, o SS é variável entre espécies (MARCELLINI et al, 2003), entre cultivares da mesma espécie (NEVES; YUHURA, 2003;SILVA et al, 2003) e até entre porções do mesmo fruto (SILVA et al, 2003).…”
Section: Resultsunclassified